Factors influencing people to approach micro finance institutions in India - N, Aarthi; M, Suresh (International Journal of Engineering and Technology, 2018)
Microfinance or Microcredit is providing financial access to the low-income people to improve their living standard and also this will en-hance the growth of national economy. Micro Finance Institutions (MFIs) provide financial services such as loan, savings, investment, insurance, money transfer and other financial products customized for low-income people. It is a highly competitive market consisting of banks, private financial institutions, local money lenders with exorbitant interest etc. Creating awareness of MFIs among the financially backward people and establishing their trust on the upcoming commercial offering is a tedious job, which requires thorough knowledge and analysis skills in addition to keen observations on the trends of financial markets. The current paper gives an insight on the factors influenc-ing common people or the driving factors to approach MFIs for their financial activities. In this paper, Interpretive Structural Modelling (ISM) approach is applied to find the interrelationships among the factors and driving power and dependence power of those factors con-cluding with most influential factors, purpose and legal elements which influences the people to approach MFIs.Â Â